1990
DOI: 10.1007/bf01289697
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy of single-proton orbitals in148Gd

Abstract: The (SHe, d) and (t, e) reactions on a radioactive Z = 64 148Gd target were used to populate the single-proton states in 149Tb and 147Eu. In 149Tb the data establish the five single-proton states of the 51 to 82 major shell. The proton occupancies deduced from these experiments suggest that in the ~48Gd ground state there are on average 1.8 (3) proton pairs above the Z = 64 shell gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The isovector SDI strength A 1 was fitted to reproduce the excitation energy of the 2 + 1 state in 134 Te. We have also considered an alternative set of proton particle energies suitable for A = 150 based on the assumption of a subshell closure at Z = 64 [35][36][37][38][39][40]. They were extracted from the excitation spectrum of 147 Tb.…”
Section: B Shell 50-82mentioning
confidence: 99%
“…The isovector SDI strength A 1 was fitted to reproduce the excitation energy of the 2 + 1 state in 134 Te. We have also considered an alternative set of proton particle energies suitable for A = 150 based on the assumption of a subshell closure at Z = 64 [35][36][37][38][39][40]. They were extracted from the excitation spectrum of 147 Tb.…”
Section: B Shell 50-82mentioning
confidence: 99%
“…The result of a g-factor measurement in Tokyo [-5] was published last year, and quite recent measurements at Orsay and Strasbourg with heavy ion beams [-6] established the much higher yrast states up to 75/2-at 13.2 MeV. 149Tb was also investigated with the (3He, d) transfer reaction [7] that populated the 5 single-proton states of the 50 to 82 shell, and a recent study of 149Dy /%decay [-8] gave detailed information on the 149Tb excitations below 2.2 MeV with spins up to 11/2. In concurrent investigations of high-spin isomer decays of N=83 isotones [9,10] it was found that the 0.5-s 27/2-3qp isomer in 149Dy has a weak Gamow-Teller/~-decay branch which selectively populates highlying non-yrast states in 149Tb. These results crucially relate to our present in-beam data, and we will discuss them in detail below.…”
Section: Introductionmentioning
confidence: 99%